A Prehistory of Hinduism - Devadevan, Manu V. (De Gruyter, 2016)
This book is a pioneering attempt to understand the prehistory of Hinduism in South Asia. Exploring religious processes in the Deccan region between the eleventh and the nineteenth century with class relations as its point of focus, it throws new light on the making of religious communities, monastic institutions, legends, lineages, and the ethics that governed them. In the light of this prehistory, a compelling framework is suggested for a revision of existing perspectives on the making of Hinduism in the nineteenth and the twentieth century.